Parsing PARP: the enzymatic and biophysical characterization of poly (ADP-Ribose) polymerases I and II - Hepler, Maggie R. D., author; Luger, Karolin, advisor; Bailey, Susan, committee member; Yao, TingTing, committee member (Colorado State University. Libraries, 2015)
The ADP-ribosyl transferase (ART) family is a prominent group of at least seventeen enzymes comprised of mono (ADP-ribose) transferases (MARTs) and poly (ADP-ribose) polymerases (PARPs). Each family member contains a conserved PARP signature motif in the catalytic domain. Enzymatically active proteins, in the presence of co-factor NAD+, catalyze individual or multiple ADP-ribose groups onto themselves or other proteins in automodification and heteromodification, respectively. The act of ADP-ribosylation implicates the ART family in a multitude of cellular processes including, but not limited to, transcription, apoptosis, DNA damage, metabolism, and inflammation. The founding member of the ART family is PARP-1, a first responder to DNA damage and regulator of active gene expression. In its inactive state and as a chromatin architectural protein, PARP-1 tightly binds chromatin, thereby regulating cellular activities, signifying the importance of PARP-1 and chromatin interaction. Importantly, PARP-1 must be activated and automodified in order to bind histones and gain nucleosome assembly function. Structurally similar and in many ways thought to be functionally redundant, PARP-2 is also thought to primarily function in the DNA damage response. PARP-2 has a non-canonical DNA binding domain, and therefore it is able to recognize different types of DNA structures in comparison to PARP-1, which could suggest a unique role for PARP-2 in repair. PARP-2 has not been extensively studied in a chromatin or gene regulation context due to this assumed redundancy. Given the pronounced functional changes in PARP-1 upon automodification, it is important to better understand what exactly triggers its enzymatic activity. Similarly, due to the functional redundancy of PARP-2, insight into activators of its enzymatic activity could indicate specificity and selectivity for the protein. However, determining the details of nuclear components that activate PARP-1 and PARP-2 are limited by the availability of a reliable quantitative and kinetic assay, as well as by the availability of defined substrates. These limitations hinder the separation of potent, and thus biologically relevant, activators from weak or non-specific activators. Utilizing a fluorescence based enzyme assay adapted for this system, kinetic parameters of PARP-1 and PARP-2 allosteric activators are reported here. As proof of principle and to test the reliability of the enzymatic assay, PARP-1 and PARP-2 activity was first tested with nucleic acids and other previously reported activators, such as nucleosomes and histones. Next, potentially novel activators were tested. Notably, PARP-1 is activated in the presence of its enzymatic product, PAR, indicating a mechanism by which PARP-1 could spread at sites of DNA damage and active gene expression. PARP-2 exhibits unique activation and specificity different from that of PARP-1 through its enzymatic preference for RNA. Further, PARP-1 remains the prominent chromatin related PARP due to the weak interaction, both activity and affinity, of chromatin with PARP-2. However, while PARP-1 and PARP-2 can act individually, affinity and activity studies demonstrate a PARP-1 and PARP-2 complex suggesting that these proteins can act sequentially and simultaneously with one another during a PAR-mediated recruitment and signaling cascade. Overall, these data indicate novel functions and mechanisms for PARP-1 and PARP-2 within the nucleus as critical responders to DNA damage and gene regulation.
Keywords: FRET; PARP-2; PARP-1; enzymology